Euro-Mediterranean science and technology collaborations: a questionnaire survey - Gaillard A.-M.; Canesse A.-A.; Gaillard J.; Arvanitis R. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
This chapter is based on the results of a questionnaire survey conducted in 2011 and addressed to a population of researchers, from both European countries and EU Mediterranean Partner Countries (hereafter referred to as MPCs), whose international collaborations/co-publications involved both the two geographical regions during the period 2005-2010. Four thousand three hundred forty (4,340) scientists filled in the questionnaire in 38 countries altogether (27 in Europe and 11 MPCs) with a balanced distribution of responses, i.e. 48% of the respondents working in Europe and 52% in the MPCs. The response rate (17%) is considered as satisfactory. Responses are heavily concentrated in larger countries: five countries, i.e. France, Italy, Spain, Germany and the United Kingdom, accounted for ¾ of the responses in Europe (74.7%), while in the MPCs the first five countries, namely Turkey, Israel, Tunisia, Algeria and Egypt, accounted for 82.6% of the responses. The main findings show that the asymmetry in collaboration, which was recognised as a source of tension and a burning issue in the 1970s and the 1980s, has developed into a more equal partnership and that international collaboration is a win-win process that benefits all partners with very significant outcomes in both regions. International collaboration addresses and involves very dedicated and goal-oriented individual scientists who seek to increase and improve their scientific capacities and develop greater international recognition.